Komplikationen im zeitlichen Verlauf nach einer operativen Wirbelsäulenversorgung - Pepke, Wojciech; Wantia, Carl; Al Mansour, Haidara; Bruckner, Thomas; Thielen, Mirjam; Akbar, Michael (Der Orthopäde, 2020)
Background. Spine surgeries can pose many complications; however, peak timing of postoperative complications in the field of spine surgery is still not sufficiently delineated in the literature as yet. Nevertheless the determination of peak timing of postoperative complications has a significant influence on patient education and postoperative follow-up. Materials and methods. This single-center study analyzed the medical records of 1179 patients that underwent spinal instrumentation between 2010 and 2015 at 3, 6, 12, 24 and 36 months postoperatively. Complications were analyzed according to their time of onset. Results. Of the 1179 patients included, 199 (16.9%) underwent revision surgery due to a complication. Peak timing for complications (72.9%) occurred within the first 3 months after surgery. Infection was the most common reason for revision surgery (42.7%) and most infections occurred within the first 3 months after surgery (early infections) (91.8% of infections). Peak timing for material failure occurred in the second post-operative year (46% of all detected prosthesis failures) (2.5% of all complications). Discussion. Peak timing of post-operative complications post spinal instrumentation occurs as early on as within the first 3 months after surgery and post-operative infections remain the most common post-operative complication overall. Nonetheless, regular and long-term postoperative clinical and radiological follow-up is crucial, since in particular prosthesis failure has its peak timing in the second post-operative year.